INVESTOR SENTIMENT AND STOCK MARKET VOLATILITY IN INDIA: A PSYCHOLOGICAL AND EMPIRICAL ANALYSIS OF INVESTMENT STRATEGIES - Chavhan, Shubham Prafulkumar; Waiker, Vinod (International Journal of Research -GRANTHAALAYAH, 2025)
With an emphasis on the psychological and empirical factors influencing investing choices, this study examines the complex link between investor sentiment and stock market volatility in the Indian setting. Key psychological elements including media impact, herd behaviour, and risk aversion are identified as important determinants of investor mood in this study, which uses a descriptive research approach and primary data gathered from 100 individual investors using structured questionnaires. Strong positive relationships between investor sentiment and market performance were found through empirical study, which included correlation and regression approaches. This suggests that emotional and cognitive biases have a substantial influence on stock market movements. The results support improved investor education and the use of sentiment research techniques, and they highlight the necessity of integrating behavioural finance insights into investing decision-making. This study adds to the expanding corpus of behavioural finance knowledge and provides useful advice for investors, advisors, and legislators on how to handle sentiment-driven market volatility.